From Household Duties to Innovation: The Role of Gender Norms in Women’s Economic Participation - Kovaleva, Irina; Taylor, Leon; Pech, Gerald; Madumarov, Eldar; Korosteleva, Anastassiya (BUKETOV BUSINESS REVIEW, 2025)
This study examines how cultural norms and household structure affect women’s participation in the labour force and their capacity to contribute to innovative activity, emphasizing patrilocality theory in Kyrgyzstan. According to the the ory, women who reside with their husband’s family are expected to spend more time on household duties and may be less likely to participate in income-generating and innovative activities outside the home. Econometric analysis uses data from the 2019 Life in Kyrgyzstan (LiK) panel survey. The Tobit model analyses the relationship between women’s living arrangements, labour force participation and earnings. The analysis reveals that, other things being equal, women earn lower wages if they have many household responsibilities; however, this does not mean that women in patrilocal living arrangements have low earnings. It also shows that education, location, and other socio-economic factors are most important in determining the rate of women’s economic participation and the innovation potential. Moreover, household decision-making power and cultural expectations are most likely to affect women’s opportunities for labour market participation. The study finds that resolving gender inequalities in domestic responsibilities and power to make decisions is crucial to unlock the potential of women in innovation for the economy. The study contributes to the exist ing literature as the first empirical analysis of these dynamics in CIS countries and as policy recommendations to pro mote gender equity and economic growth.